The relationship between excess returns, firm size and earnings on the Johannesburg Stock Exchange - Michael J. Page; Francis Palmer (South African Journal of Business Management, 1991)
While considerable empirical work has been conducted in the United States concerning excess returns and the relationship of these returns to firm size and E/P ratio, thus far, there have been few similar empirical studies conducted using Johannesburg Stock Exchange (JSE) data. Evidence of firm size or E/P ratio effects has been ascribed by various authors to either model misspecification or market inefficiencies. In this article the evidence is examined for the South African market using 1370 company years of data over the period 1978 to 1988, and a significant earnings effect is found, but no size effect. In the analysis the problem of data bias is considered with particular emphasis on thin trading Issues, and a methodology for future empirical work is described. Finally, it is suggested that the evidence can be better explained by market inefficiencies than model misspecification.
Keywords: 650